1996
DOI: 10.1152/jappl.1996.81.5.2134
|View full text |Cite
|
Sign up to set email alerts
|

Subnormal norepinephrine release relates to presyncope in astronauts after spaceflight

Abstract: Postflight orthostatic intolerance is experienced by virtually all astronauts but differs greatly in degree of severity. We studied cardiovascular responses to upright posture in 40 astronauts before and after spaceflights lasting up to 16 days. We separated individuals according to their ability to remain standing without assistance for 10 min on landing day. Astronauts who could not remain standing on landing day had significantly smaller increases in plasma norepinephrine levels with standing than did those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
202
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(217 citation statements)
references
References 25 publications
14
202
1
Order By: Relevance
“…shown that astronauts who are orthostatic intolerant exhibit a significantly lower norepinephrine response to standing than their tolerance counterparts (Fritsch-Yelle et al 1996).…”
Section: Cardiovascular System and Deconditioningmentioning
confidence: 99%
“…shown that astronauts who are orthostatic intolerant exhibit a significantly lower norepinephrine response to standing than their tolerance counterparts (Fritsch-Yelle et al 1996).…”
Section: Cardiovascular System and Deconditioningmentioning
confidence: 99%
“…8 On the other hand, women (all non-finishing) were shown to have the ability to increase their TPR from supine to standing by margins even larger than most male finishers, but had lower pretest TPR and blood pressure, as well as a higher arterial pressure threshold at which presyncope occurred. 18 This comparison suggests that while an increase in TPR may be necessary to maintain arterial pressure and prevent presyncope, it may be insufficient if pretest arterial pressure is too near to its presyncopal threshold.…”
Section: Introductionmentioning
confidence: 97%
“…However, on return to earth, from one-quarter to twothirds of them have reduced orthostatic tolerance for a few weeks. The underlying molecular mechanisms remain unknown and are probably multifactorial, although alterations in the autonomic nervous system and/or neuromuscular function after spaceflight probably contribute to this problem (18,19).…”
Section: +mentioning
confidence: 99%
“…Many astronauts suffer to varying degrees from symptoms suggestive of autonomic dysfunction such as nausea, vomiting, and dizziness during the early days of space flight (17), as well as showing severe orthostatic intolerance for several days after spaceflight (18,19). The underlying molecular mechanism and appropriate treatment for the autonomic dysfunction in space and on earth after space flight remain unknown.…”
Section: Introductionmentioning
confidence: 99%